Pengaruh Struktur Aktiva, Debt to Asset Ratio, Total Asset Turnover dan Return On Asset terhadap Price Book Value - Amanda Sulistia; Priyambada Bagus Artanta (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This study aims to determine the effect of Asset Structure, Debt to Asset Ratio, Total Asset Turnover and Return On Asset on the Price Book Value in advertising, printing and media sub-sector companies listed on the Indonesian Stock Exchange for the 2018-2022 period. This research is a type of descriptive research with quantitative methods. The sampling technique for this research uses a purposive sampling method, so that a sample consisting of 15 advertising, printing and media sub-sector companies listed on the Indonesian Stock Exchange for the 2018-2022 period is obtained. The data collection technique for obtaining secondary data is documentation. The analysis technique used in this research is multiple linear regression analysis with the help of the SPSS program. The limitation in the study is that the share price used to calculate the Price Book Value is the closing share price at the end of the year. so further researchers are advised to use share prices other than the closing share price at the end of the year, for example the average share price per month. The results showed that Asset Structure and Total Asset Turnover had an effect on Price Book Value, while Debt to Asset Ratio and Return On Asset had no effect on Price Book Value.